2018
DOI: 10.3389/fchem.2018.00239
|View full text |Cite
|
Sign up to set email alerts
|

Structure Properties, Acquisition Protocols, and Biological Activities of Oleuropein Aglycone

Abstract: Oleuropein aglycone, which is the major phenolic component of extra virgin olive oil, is gaining popularity and importance in scientific and public communities. This paper summarizes the structure properties, acquisition protocols, and biological activities of oleuropein aglycone. There are three hydrolytic methods used to obtain oleuropein aglycone from oleuropein-enzymatic hydrolysis, acid hydrolysis, and acetal hydrolysis. Enzymatic hydrolysis can be achieved with exogenous enzymes and endogenous enzymes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 63 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Besides this, several studies have reported the positive role of OL in improving cognitive anomalies in animal models. This improvement in cognition after OL intake was considered as its role in modulation of the autophagy pathways (Xu et al., 2018). To explore this hypothesis, the first effort was made by Grossi and his co‐workers.…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…Besides this, several studies have reported the positive role of OL in improving cognitive anomalies in animal models. This improvement in cognition after OL intake was considered as its role in modulation of the autophagy pathways (Xu et al., 2018). To explore this hypothesis, the first effort was made by Grossi and his co‐workers.…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…Oleuropein aglycon, is liberated in the course of oleuropein de-glycosylation [45]. Research demonstrated that oleuropein aglycon has a great contribution to developing bitterness/astringency [46].…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Moreover, a reduction in the number and size of Aβ(1–42) plaques present in the brain cortex of the treated animals was found. In light of the above findings we can conclude that oleuropein aglycone compensates for Aβ aggregation and modulates the neurotoxicity attributed to the last of them and disturbs diverse pathways such as the processing of amyloid precursor proteins, the amyloid-β and tau protein aggregates, autophagy damage and neuroinflammation [39].…”
Section: Low-molecular Weight Compounds Tested For Decreasing Amylmentioning
confidence: 99%